WIRELESS TABLET - THE PART OF INTERACTIVE TEACHING SYSTEMS - KROTKY, JAN (Trends in education, 2008)
Wireless tablets which are used in education mean the interesting alternative to improve the education. These instruments mean the way to interactive entering to teaching and make the new ways in make-up of teaching materials. Author of the article shows some ideas and ways of using these instrumets mainly in teaching in basic schools. These problems are part of developing project MSMT which is solving in KAT ZCU. This project is solving in new center of digital multimedial teaching technologies (www.cdmvt.zcu.cz).
Keywords: Tablet; Interactive Board; InterWrite; BlueTooth